Applying a 3D Dipole Model for Lightning Electrodynamics of Low-Flying Aircraft - Fisher, J.; Hoole, P.R.P.; Pirapaharan, K.; Ratnajeevan, S.; Hoole, H. (IETE JOURNAL OF RESEARCH, 2015)
In this paper we apply a detailed electrostatic model of an aircraft to be used in an experimentally validated, new elec- tric-charge-based circuit model for studying aircraft-lightning electrodynamics. The model is used to evaluate the elec- trodynamics of an aircraft under a thundercloud. As commercial and military aircraft continue to be subject to direct lightning flashes, we have previously developed a dipole model to characterize electrical currents and electric potential fluctuations on an aircraft for alternative design strategies to minimizing the severity of lightning-aircraft dynamics. With the increased severity of thunderstorms due to global warming, the need to predict and quantify electrical char- acteristics of the lightning-aircraft electrodynamics is greater, but they are normally not measurable. That dipole model is used here in a new a simple matrix formulation and applied to low-flying aircraft to compute the lightning channel voltages and currents after the aircraft is struck by lightning.
Keywords: Aircraft; Dipole modelling; Electrodynamics; Lightning; Transmission line modelling